Analysis of the Babesia microti proteome in infected red blood cells by a combination of nanotechnology and mass spectrometry. Issue 2 (February 2019) - Magni, Ruben; Luchini, Alessandra; Liotta, Lance; Molestina, Robert E.
Graphical abstract: Highlights: Babesiosis has been recognized as an emerging infectious disease in the United States. Proteomic analysis of Babesia microti infection in whole blood is a challenge. Advances in nanotechnology and mass spectrometry can circumvent the analytical roadblocks. This is the first known report to present a proteome description of B. microti in vivo. Abstract: Proteomics of Babesia microti has lagged behind other apicomplexans despite recent genome and transcriptome studies. Here, we used a combination of nanotechnology and mass spectrometry to provide a proteomic profile of B. microti acute infection. We identified ∼500 parasite proteins in blood with functions such as transport, carbohydrate and energy metabolism, proteolysis, DNA and RNA metabolism, signaling, translation, lipid biosynthesis, and motility and invasion. We also identified surface antigens with roles in the immune response to the parasite. This first evaluation of the B. microti proteome in erythrocytes provides information for the study of intracellular survival and development of diagnostic tools using mass spectrometry.